Uncontrolled Type 2 Diabetes Mellitus with Multicomorbidities in a 58-Year-Old Woman : A Case Report - Hevy Purwaningtyas, Nuretha; Adi Nugroho, Satrio (Family Medicine Department, Faculty of Medicine, Brawijaya University, 2026)
Type 2 Diabetes Mellitus (T2DM) is a chronic disease with high global prevalence, and uncontrolled cases often result in multiple comorbidities and reduced quality of life. Family medicine provides a holistic approach by integrating biomedical, psychosocial, and environmental perspectives into management. This case report describes a 58-year-old overweight woman with a genetic predisposition who presented with uncontrolled T2DM complicated by neuropathy, pruritus, chronic gastritis, low back pain, and vertigo. Data were collected through clinical encounters, patient interviews, medical records, family assessment tools (Family APGAR, SCREEM, Mandala of Health), and home visits at Dinoyo, Malang, in September 2025. Family assessment revealed strong support but limited financial resources. Management included pharmacological adjustments, dietary counseling, physical activity promotion, and family–community engagement. This case highlights how a holistic family medicine approach can improve adherence, address risk factors, and achieve better outcomes in patients with uncontrolled T2DM and multiple comorbidities.